Constraining the anomalous Higgs boson coupling in production *Supported by the National Natural Science Foundation of China (11875278), Beijing Municipal Science & Technology Commission (Z181100004218003), the National Key Research and Development Program of China (2018YFA0404001), and the Hundred Talent Program of the Chinese Academy of Sciences (Y6291150K2). (April 2019) - Shi 石, Liaoshan 辽珊; Liang 梁, Zhijun 志均; Liu 刘, Bo 波; He 何, Zhenhui 振辉
Abstract: Higgs boson production in association with a photon ( H + ) offers a promising channel to test the Higgs boson to photon coupling at various energy scales. Its potential sensitivity to anomalous couplings of the Higgs boson has not been explored with the proton-proton collision data. In this paper, we reinterpret the latest ATLAS H + resonance search results within the Standard Model effective field theory (EFT) framework, using 36.1 fb −1 of proton-proton collision data recorded with the ATLAS detector at TeV. Constraints on the Wilson coefficients of dimension-six EFT operators related to the Higgs boson to photon coupling are provided for the first time in the H + final state at the LHC.